Self-Assessment in the inland expansion of Graduate Studies in Education in the Semi-Arid Region of Ceará: from the MAIE Program to PPGEEN-UECE (Práxis Educativa, 2025)
This article aims to analyze the process of self-assessment and strategic planning in the Intercampus Academic Master’s in Education and Teaching (MAIE, acronym in Portuguese), from 2013 to 2024. The qualitative and documentary methodology is based on the synthesis of MAIE’s Strategic Plans and the self-assessment process, as well as on meeting minutes, MAIE’s quadrennial evaluation reports, the Working Group report on self-assessment of the Brazilian Coordination for the Improvement of Higher Education Personnel (CAPES), The Institutional and Pedagogical Development Plans of the State University of Ceará (UECE) – 2017 to 2026, the National Graduate Plan, the New Course Proposal Evaluation (APCN) of MAIE and of the Graduate Program in Education and Teaching (PPGEEN), in addition to studies such as Campos (2025), Freire (1987, 2021), Gramsci (1982), Leite et al. (2020), Magalhães, Garcia and Huet (2024), Polidori and Rodrigues (2024), among others. The findings indicate that the self-assessment process and strategic planning strengthened both the program and its faculty board, promoted integration with alumni and society, and enabled the achievement of collectively defined objectives and goals.Keywords: Self-assessment. Graduate Studies in Education. Intercampus Master’s Degree in Education and Teaching.